No words : a novel - Cabot, Meg (Cabot, Meg. Little Bridge Island series, 2021)
Jo Wright always swore she'd never step foot on Little Bridge Island, not as long as her nemesis, bestselling author Will Price, is living there. Then Jo's given an offer she can't refuse: an all-expense paid trip to speak and sign at the island's first ever book festival. Even though arrogant Will is the last person Jo wants to see, she could really use the festival's more-than-generous speaking fee. She's suffering from a crippling case of writer's block on the next installment of her bestselling children's series, and her father needs financial help as well. Then Jo hears that Will is off-island on the set of the film of his next book. Hallelujah! But when she arrives on Little Bridge, Jo is in for a shock: Will is not only at the book festival, but seems genuinely sorry for his past actions, and more than willing not only to make amends, but prove to Jo that he's a changed man. Things seem to be looking up, until disaster strikes, causing Jo to wonder: Do any of us ever really know anyone?